Prefaces by King Rama VI: Deflections of the Role as a Great Literary Scholar - Jatuthasri, Thaneerat (Journal of International Studies, Prince of Songkla University, 2012)
This article aims to explore the role of King Rama VI as a literary scholar reflected from his fifteen prefaces chosen to be studied. The study finds that the prefaces of King Rama VI share the same content in which explicitly reflects the role and characteristics of the king as a great literary scholar. The content of the prefaces reflects that the king is an expert in literature who could explain and clarify the knowledge of literature very well as well as could criticize his own literary works without prejudice. His prefaces also reveal that the king strongly encorages and supports the publication of both Thai and foreign literature.